The Empowerment Model of Coastal Homestay Business Owners in Five Strategic Areas of National Tourism - Arevin, Ayat Taufik; Sarna, Ma'Mun; Asngari, Pang S.; Pudji Mulyono, Pudji Mulyono (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2014)
This study examines the variables related and having influence on the success of the coastal homestay business owners. The total number of samples is 160 owners in five areas of KSPN (the Strategic Area of Indonesian National Tourism) namely: Pangandaran, Parangtritis, Karangasem, Pulau Untung Jawa, and Tanjung Lesung-UKNP. The hypotheses are: (1) individual and environmental characteristics influence the process of extensions, working-competence, and entrepreneurial behavior; (2) the extension process has real influence on working-competence and business empowerment; (3) working competence positively influence entrepreneurial behavior and empowerment; (4) Entrepreneurial behavior and empowermen directly affect the success of business, and (5) Empowerment clearly affects business success. The model evaluation throug bootstrapping technique gives a reference that: (1) the level of effectiveness of the extension process is influenced by age, cosmopolitan level, the role of community leaders, and cultural value systems; (2) the role of extension institutions and method contributes to the increased working-competence and entrepreneurial behavior. (3) working-competence is reflected in the ability to handle reservations, receptions, and housekeeping; (4) the entrepreneurial behavior is reflected by transparency, th level of discipline, punctuality and tenacity; and (5) business success becomes more effective through entrepreneurial behavio than the level of empowerment.